Comparison of acidic and neutral PH root conditioners prior to a coronally positioned flap to treat gingival recession - Roya Shariatmadar Ahmadi; Mohammd Reza Awwadi; Shilan Moatazed; Fatemeh Rezaei; Samira Hajisadeghi (Wolters Kluwer Medknow Publications, 2014)
Background: Localized gingival recession can be treated successfully via coronally positioned flap (CPF) and additional use of root surface demineralization agents. The purpose of this study was to evaluate the effects of additional use of ethylene diamine tetraacetic acid (EDTA) and citric acid as a root conditioner in association with CPF to cover localized buccal gingival recessions. Materials and Methods: Twenty-seven patients with 66 Miller class I buccal gingival recession ≥ 2 mm on single-rooted teeth were studied. Patients were randomly assigned: CPF with EDTA gel (test 1) and CPF with saturated citric acid (test 2) or CPF alone (control). Clinical parameters were measured at baseline and 1, 2, 3 and 6 months after surgery; assessment included recession depth (RD), clinical attachment level (CAL), probing depth (PD) and height of keratinized gingiva (HKG). SPSS version-20 was used to perform all statistical analyses. Data was reported as Mean ± SD. Age, RD, CAL, PD, and HKG before treatment and after 6 months among study groups were compared by one-way ANOVA followed by the Tukey test. The level of significance was considered to be less than 0.05. Results: At 6 months, all treatment modalities showed significant root coverage and gain in CAL. RD was reduced from 2.86 ± 0.76 mm to 0.55±0.53 mm in the EDTA group and from 2.37±0.57 mm to 1.03±0.43 mm in the acid group and from 2.37±0.54 mm to 0.85±0.49 mm in the control group. The average percentage of root coverage for the EDTA, acid, and control groups were 80.73%, 52.16%, and 64.50%, respectively. At 6 months, there was a significant difference (P < 0.05) in all parameters for the EDTA group (except HKG that did not vary among the groups). Conclusion: Root preparation with EDTA was an effective procedure to cover localized gingival recessions and significantly improved the amount of root coverage obtained.